STUDI PERBANDINGAN KINERJA KEUANGAN ANTARA PERBANKAN SYARIAH DI INDONESIA DAN MALAYSIA SELAMA PANDEMI COVID-19 - Arina Aula Harfina; Agung Budi Sulistiyo; Septarina Prita Dania Sofianti (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2023)
This study aims to examine and analyze the differences between the financial performance of Islamic banking between 2 (two) countries, namely Indonesia and Malaysia during the Covid-19 pandemic. This research is a quantitative study that examines the difference between financial performance during Covid-19 and the financial ratios of Indonesia and Malaysia using the ratio of Return on Assets (ROA), Capital Adequacy Ratio (CAR), Non Performing Loans (NPF), and Financing to Deposit Ratio ( FDR). This study uses secondary data obtained from the financial statements of each Indonesian and Malaysian Islamic banking. Based on the purposive sampling method, the sample used was 25 Islamic banks, consisting of 13 Indonesian Islamic banks and 12 Malaysian Islamic banks. Hypothesis testing in this study used the Independent sample t-test and the Mann Whitney test. The results of this study are that during the Covid-19 pandemic between Indonesian and Malaysian Islamic banking there was a significant difference in the CAR ratio, and for the ratios of ROA, NPF and FDR there were no significant differences.Keywords: covid-19 pandemic, financial performance, financial ratios, islamic banking ABSTRAKPenelitian ini bertujuan untuk menguji dan menganalisis perbedaan antara kinerja keuangan perbankan syariah diantara 2 (dua) negara yaitu Indonesia dan Malaysia selama pandemi Covid-19. Penelitian ini merupakan penelitian kuantitatif yang menguji perbedaan antara kinerja keuangan selama Covid-19 terhadap rasio keuangan Indonesia dan Malaysia menggunakan rasio Return of Asset (ROA), Capital Adequacy Ratio (CAR), Non Performing Loan (NPF), dan Financing to Deposit Ratio (FDR). Penelitian ini menggunakan data sekunder yang diperoleh dari laporan keuangan masing-masing perbankan syariah Indonesia dan Malaysia. Berdasarkan metode pemilihan sampel purposive sampling, sampel yang digunakan berjumlah 25 perbankan syariah, yang terdiri dari 13 perbankan syariah Indonesia dan 12 perbankan syariah Malaysia. Pengujian hipotesis dalam penelitian ini menggunakan uji beda Independent sample t-test dan uji Mann whitney. Hasil penelitian ini adalah pada masa pandemi Covid-19 antara perbankan syariah Indonesia dan Malaysia terdapat perbedaan yang signifikan pada rasio CAR, dan untuk rasio ROA, NPF dan FDR tidak terdapat perbedaan yang signifikan.Kata Kunci: kinerja keuangan, pandemi covid-19, perbankan syariah, rasio keuangan